Respuesta :

1/128(3-4cos(2x)+(4x))

Answer:

(2x)^2 - (3)^2 = (2x - 3)(2x + 3)

a^2 - b^2 = (a -b)(a +b). This is called "difference of squares identity."

Step-by-step explanation:

The given expression is [tex]4x^2 - 9[/tex]

We have to use the identity a^2 - b^2 = (a -b)(a +b). This is called "difference of squares identity."

We can write 4x^2 = (2x)^2 and 9 = (3)^2

So we can write the given expression as (2x)^2 - (3)^2

Using the difference of squares identity, we can factor it as

(2x)^2 - (3)^2 = (2x - 3)(2x + 3)